A long-term controlled drug-delivery with anionic beta cyclodextrin complex in layer-by-layer coating for percutaneous implants devices - Verza, Beatriz S. [UNESP] (2021)
This study demonstrated a drug-delivery system with anionic beta cyclodextrin (β-CD) complexes to retain tetracycline (TC) and control its release from multilayers of poly(acrylic acid) (PAA) and poly(l-lysine) (PLL) in a ten double layers ([PAA/PLL]10) coating onto titanium. The drug-delivery capacity of the multilayer system was proven by controlled drug release over 15 days and sustained released over 30 days. Qualitative images confirmed TC retention within the layer-by-layer (LbL) over 30 days of incubation. Antibacterial activity of TC/anionic β-CD released from the LbL was established against Staphylococcus aureus species. Remarkably, [PAA/PLL]10/TC/anionic β-CD antibacterial effect was sustained even after 30 days of incubation. The non-cytotoxic effect of the multilayer system revealed normal human gingival fibroblast growth. It is expected that this novel approach and the chemical concept to improve drug incorporation into the multilayer system will open up possibilities to make the drug release system more applicable to implantable percutaneous devices.